Translation direction is not correct (Journal of actual problems of jurisprudence, 2018)
In the article general обьекты is considered overcame by the organized crime in Republics of Kazakhstanand counteractions at the level of public organs.Keywords: Organizational crimes, organizational criminal group, economic crimes, corruption crimes